The Correlations among English Teachers’ TPACK, TISE, ITOE, and Teaching Implementation - Sofendi, Sofendi; Vianty, Machdalena; Randika, Aresti (Jurnal Pendidikan Progresif, 2020)
The Correlations among English Teachers’ TPACK, TISE, ITOE, and Teaching Implementation. Objectives: This research is correlational research that aimed to find out the correlations among Technological Pedagogical Content Knowledge (TPACK), Technology Integration Self-Efficacy (TISE), Instructional Technology Outcome Expectation (ITOE), and Teaching Implementation. Methods: TPACK-EFL Survey and Motivation of Technology Integration in Education Scale Questionnaires were distributed to 60 students of the English language teacher professional education program at Sriwijaya University in the academic year 2018/2019. Findings: The findings of this research showed that the students have a high understanding level of TPACK, high level of TISE, high level of ITOE, and good in teaching implementation, and there are positive significant correlations among TPACK, TISE, ITOE, and teaching implementation. Conclusion: Not only the technical equipment but also the qualified teachers who understand how to advance the ICT are very needed. Therefore, both understanding TPACK and acquiring TISE-ITOE are necessary. Keywords: Teacher Professional Education Program (PPG), TPACK, TISE, ITOE. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202013